Sex‐specific density‐dependent secretion of glucocorticoids in lizards: insights from laboratory and field experiments. Issue 7 (15th February 2017) - Mugabo, Marianne; Galliard, Jean‐François Le; Perret, Samuel; Decencière, Beatriz; Haussy, Claudy; Meylan, Sandrine
Abstract : Negative density feedbacks have been extensively described in animal species and involve both consumptive (i.e. trophic interactions) and non‐consumptive (i.e. social interactions) mechanisms. Glucocorticoids are a major component of the physiological stress response and homeostasis, and therefore make a good candidate for proximate determinants of negative density feedbacks. Here, we combined laboratory and field experiments with enclosed populations to investigate the relationship between density, social stress and plasma corticosterone levels in the common lizard Zootoca vivipara . This species exhibits strong negative density feedbacks that affect females more than males, and its life history is sensitive to experimentally‐induced chronic elevation of corticosterone plasma levels. We found that prolonged crowding in the laboratory can trigger a chronic secretion of corticosterone independent from food restriction. In the field experiments, corticosterone levels of females were not affected by population density. Corticosterone levels of males increased with population density but only during the late activity season in a first field experiment where we manipulated density. They also increased with density during the mating season but only in populations with a female‐biased sex ratio in a second field experiment where we crossed manipulated density and adult sex ratio. Altogether, our results provide limited evidence for a role of basal corticosterone secretion in density feedbacks in this species. Context and density‐dependent effects in males may arise from changes in behavior caused by competition for resources, male–male competition, and mating.